Mothers in Trouble: Coping with Actual or Pending Separation From Children Due to Incarceration - Celinska, Katarzyna (2010)
Although female offenders are the fastest growing population in prison today, relatively few studies focus on their unique experiences as mothers. In this study, the authors utilize 74 semistructured interviews with mothers before trial and during incarceration to document coping strategies employed to deal with potential or actual separation from their children. From the study data, seven strategies emerge: being a good mother, mothering from prison, role redefinition, disassociation from prisoner identity, self-transformation, planning and preparation, and self-blame. The findings show that mothers used multiple strategies and tended to employ emotion-focused and adaptive coping techniques. The policy implications are discussed